INTEREST IN USING E-FILING: ANTECEDENTS AND CONSEQUENCES ON PERSONAL TAXPAYER COMPLIANCE (Study at KPP Pratama West Semarang) - Aquilla Nency Ditya; Maria Goreti Kentris Indarti (SEAN Institute, 2023)
The purpose of this study was to determine the effect of perceive usefulness, perceived ease of use, perceived security and confidentiality on the interest of taxpayers in the use of e-filing and individual taxpayer’s compliance. The population used in this study were individual taxpayers registered at the West Semarang KPP Pratama in 2022 as many as 43.948 individual taxpayers. The number of samples in this study were 110 individual taxpayers. The research method uses multiple linear regression. The results of the analysis show that perception of usefulness influence the interest of taxpayers in the use of e-filing. Perception of ease of use influence the interest of taxpayers in the use of e-filing. Perception of security and confidentiality influence the interest of taxpayers in the use of e-filing. The interest of taxpayers in the use of e-filing influence individual taxpayer compliance.